Variation of the Infrahyoid Muscle: Duplicated Omohyoid and Appearance of the Levator Glandulae Thyroideae Muscles - Kim, Deog-Im; Kim, Ho-Jeong; Park, Jae-Young; Lee, Kyu-Seok (Yonsei medical journal, 2010)
The embryologic origin of the omohyoid muscle is different from that of the other neck muscles. A number of variations such as the absence of muscle, variable sites of origin and insertion, and multiple bellies have been reported. However, variations in the inferior belly of the omohyoid muscle are rare. There have been no reports of the combined occurrence of the omohyoid muscle variation with the appearance of the levator glandulase thyroideae muscle. Routine dissection of a 51- year-old female cadaver revealed a duplicated omohyoid muscle and the appearance of the levator glandulae thyroideae muscle. In this case, the two inferior bellies of the omohyoid muscle were found to originate inferiorly from the superior border of the scapula. One of the inferior bellies generally continued to the superior belly with the tendinous intersection. The other inferior belly continued into the sternohyoid muscle without the tendinous intersection. In this case, the levator glandulae thyroideae muscle appeared on the left side, which attached from the upper border of the thyroid gland to the inferior border of the thyroid cartilage. These variations are significant for clinicians during endoscopic diagnosis and surgery because of the arterial and nervous damage due to iatrogenic injuries. The embryologic origins of the omohyoid and levator glandulae thyroideae muscles may be similar based on the descriptions in the relevant literature.